2018
DOI: 10.1073/pnas.1803177115
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1 ensures genome integrity by eliminating estrogen-induced pathological topoisomerase II–DNA complexes

Abstract: Women having BRCA1 germ-line mutations develop cancer in breast and ovary, estrogen-regulated tissues, with high penetrance. Binding of estrogens to the estrogen receptor (ER) transiently induces DNA double-strand breaks (DSBs) by topoisomerase II (TOP2) and controls gene transcription. TOP2 resolves catenated DNA by transiently generating DSBs, TOP2-cleavage complexes (TOP2ccs), where TOP2 covalently binds to 5′ ends of DSBs. TOP2 frequently fails to complete its catalysis, leading to formation of pathologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
96
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(103 citation statements)
references
References 67 publications
(83 reference statements)
7
96
0
Order By: Relevance
“…[52]. As we experienced low IP efficiency with commercial SMC5 antibodies, we tagged endogenous SMC5 alleles C-terminally with the mAID-EGFP tag in human TK6 cells using CRISPR-Cas9, using the strategy reported in Ref.…”
Section: Smc5/6 Physically Interacts With Fancd2-i In Human Cellsmentioning
confidence: 99%
“…[52]. As we experienced low IP efficiency with commercial SMC5 antibodies, we tagged endogenous SMC5 alleles C-terminally with the mAID-EGFP tag in human TK6 cells using CRISPR-Cas9, using the strategy reported in Ref.…”
Section: Smc5/6 Physically Interacts With Fancd2-i In Human Cellsmentioning
confidence: 99%
“…phosphodiesterases (TDPs) that hydrolyze the covalent tyrosine-DNA bond, with TDP1 excising TOP1-DPCs (Pouliot et al, 1999) and TDP2 excising TOP2-DPCs in higher eukaryotes (Cortes Ledesma et al, 2009). In additions to TDPs, endonucleases such as Mre11 and XPF have been reported to play a key role in removing both TOP-DPCs presumably by incising the DNA adjacent to the TOP-DPC (Aparicio et al, 2016;Pommier et al, 2016;Sasanuma et al, 2018). Proteolytic degradation is required for TDP activities and earlier work showed that the ubiquitin (Ub)proteasome pathway (UPP) plays an important role in proteolyzing TOP-DPCs (Desai et al, 1997;Mao et al, 2001).…”
mentioning
confidence: 99%
“…If HR is not available, in contrast to the "clean" end processing mediated by TDP2, endonucleases would potentially generate the loss of information at DNA ends (Figure 1). However, it has been shown that MRE11, the nuclease activity of the MRN complex, can process abortive TOP2 DSBs regulated by a HR-independent role of BRCA1 (Hoa et al, 2016;Sasanuma et al, 2018). Notably, MRE11 H129N (nuclease deficient) mutants exhibit increased instability and translocations when treated with TOP2 poisons (Sasanuma et al, 2018;Gothe et al, 2019).…”
Section: Illegitimate Top2 Dsb Repairmentioning
confidence: 99%
“…However, it has been shown that MRE11, the nuclease activity of the MRN complex, can process abortive TOP2 DSBs regulated by a HR-independent role of BRCA1 (Hoa et al, 2016;Sasanuma et al, 2018). Notably, MRE11 H129N (nuclease deficient) mutants exhibit increased instability and translocations when treated with TOP2 poisons (Sasanuma et al, 2018;Gothe et al, 2019). The contribution of MRE11 and other nucleases such as ARTEMIS in the repair of physiological levels of TOP2 breaks, their relevance in TOP2 poison-based chemotherapy and their implication in TOP2-induced genome instability is under discussion.…”
Section: Illegitimate Top2 Dsb Repairmentioning
confidence: 99%